(untitled) (Scientific journal of the Fergana State University, 2024)
This article discusses the pedagogical stages of developing the aesthetic competence of future educators in preschool educational organizations and the role of educating them in an aesthetic spirit through music education in the composition of components, the role of music training in the lives of future educators.